A structure and evolutionary-based classification of solute carriers - Ferrada, Evandro; Superti-Furga, Giulio (iScience, 2022)
Solute carriers are an operationally defined diverse family of membrane proteins involved in the transport of nutrients, metabolites, xenobiotics, and drugs. Here, we provide an integrative classification of solute carriers by combining evolutionary information with proteome-wide structure models recently made available through the AlphaFold resource. Analyses of orthologous relations among 455 protein-coding genes currently classified as human solute carriers, over the fully sequenced genomes of 2,100 species, suggest no more than approximately 180 independent evolutionary origins. Structural comparative analyses provided further insight revealing a total of 24 structurally distinct transmembrane folds, increasing by approximately 40% the number of previously described SLC structural folds. In addition, a structural comparative analysis identified a new human solute carrier member and revealed details of noncanonical ones. Our analyses uncover new ancestral relations between solute carrier genes, provide insights into the evolution of remote homologs and a platform to test hypotheses of functional deorphanization. [Display omitted] •A classification of SLC genes based on structure and evolutionary information•Experimental and Alpha-Fold models reveal the structural diversity of solute carriers•New associations between orphan genes and members of characterized SLC families•A previously unidentified SLC gene member of the nucleoside-sugar transport family Biological sciences; Biochemistry; Classification of proteins; Evolutionary biology